The association between individual radiographic findings and improvement after chiropractic spinal manipulation and home exercise among older adults with back-related disability: a secondary analysis - Michele J. Maiers; Andrea K. Albertson; Christopher Major; Heidi Mendenhall; Christopher P. Petrie (Chiropractic & Manual Therapies)
Abstract Background Some chiropractors use spinal x-rays to inform care, but the relationship between radiographic findings and outcomes is unclear. This study examined the association between radiographic findings and 30% improvement in back-related disability in older adults after receiving 12 weeks of chiropractic spinal manipulation and home exercise instruction. Methods This IRB-approved secondary analysis used randomized trial data of community-dwelling adults age ≥ 65 with chronic spinal pain and disability. Data were collected during the parent trial between January 2010-December 2014. The primary outcome of the parent study was ≥ 30% improvement in Oswestry Disability Index (ODI) at 12 weeks, a clinically important response to care. In this secondary analysis, two chiropractic radiologists independently assessed digital lumbar radiographs for pre-specified anatomic, degenerative, and alignment factors; differences were adjudicated. The unadjusted association between baseline radiographic factors and 30% ODI improvement was determined using chi-square tests. Results From the parent trial, 120 adults with baseline lumbar radiographs were included in this study. Mean age was 70.4 years (range 65–81); 59.2% were female. Mean baseline disability (ODI = 25.6) and back pain (5.2, 0–10 scale) were moderate. Disc degeneration (53.3% moderate, 13.3% severe), anterolisthesis (53.3%), retrolisthesis (36.6%) and scoliosis (35.0%) were common among the participant sample. After 12-weeks of treatment, 51 (42.5%) participants achieved 30% improvement in back disability. No alignment, degenerative, or anatomic factors were associated with ODI improvement at 12 weeks (all p > 0.05), regardless of severity of radiographic findings. Conclusion We found no association between a predetermined subset of radiographic findings and improvement in back-related disability among this sample of older adults. As such, this study provides preliminary data suggesting that imaging may be unhelpful for predicting response to chiropractic spinal manipulation and home exercise.